Towards a Model of Translation Competence - Campbell, Stuart (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1991)
AbstractTranslation tests are discussed to determine the extent to which they assess translation competence and reveal translation processes rather than comparisons between source and target texts. An outline of a model of translation competence is suggested, and further developed through a case study, which proposes components of translation competence and a developmental schema. Finally a model of translation competence is proposed, and suggestions are made in the light of the model about translation testing and curriculum design.